2012
DOI: 10.1101/gad.184663.111
|View full text |Cite
|
Sign up to set email alerts
|

The DNA helicase Pfh1 promotes fork merging at replication termination sites to ensure genome stability

Abstract: Bidirectionally moving DNA replication forks merge at termination sites composed of accidental or programmed DNA-protein barriers. If merging fails, then regions of unreplicated DNA can result in the breakage of DNA during mitosis, which in turn can give rise to genome instability. Despite its importance, little is known about the mechanisms that promote the final stages of fork merging in eukaryotes. Here we show that the Pif1 family DNA helicase Pfh1 plays a dual role in promoting replication fork terminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 43 publications
7
85
0
Order By: Relevance
“…S5). Thus, DNA lesion hotspots in pfh1-R20 are intimately related to Pol III genes, consistent with the known role of Pfh1 in overcoming replication block at Pol III genes (Sabouri et al 2012;Steinacher et al 2012).…”
Section: Rad52 Enrichment Patterns In Pfh1 Helicase Mutantssupporting
confidence: 49%
See 2 more Smart Citations
“…S5). Thus, DNA lesion hotspots in pfh1-R20 are intimately related to Pol III genes, consistent with the known role of Pfh1 in overcoming replication block at Pol III genes (Sabouri et al 2012;Steinacher et al 2012).…”
Section: Rad52 Enrichment Patterns In Pfh1 Helicase Mutantssupporting
confidence: 49%
“…3D). We suspect this correlation is related to the observations that in Pfh1-depleted cells tRNA genes became polar fork barriers that caused stronger elevation of replication pausing and recombination when replication and transcription move in opposite directions (Sabouri et al 2012;Steinacher et al 2012). …”
Section: Rad52 Enrichment Patterns In Pfh1 Helicase Mutantsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there are differences between the two studies. For example, Steinacher et al (2012) saw heightened pausing at only one of the four rDNA Ter sites, while our data are best explained by increased pausing at all four Ter sites (Fig. 2C).…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, by genetic criteria, it is extremely difficult to eliminate nuclear Pfh1 (Pinter et al 2008). Another study also found replication defects in rDNA in Pfh1-depleted cells (Steinacher et al 2012). However, there are differences between the two studies.…”
Section: Discussionmentioning
confidence: 91%